(untitled) (The Pakistan Development Review, 1995)
Agriculture research and development efforts in Pakistan have traditionally been focused on raising the farm productivity of irrigated areas. Among other factors, the underlying causes for this irrigated bias could be attributed to: the importance given to the irrigated areas in the overall planning framework; the dominance of the irrigated farm lobby at all levels of research, politics, and government; the relative progressiveness of irrigated farmers in terms of adoption of new technologies; and the presence of risk-reducing natural conditions prevailing on irrigated farms, e.g., certainty of subsidised water supply when it is most needed. Further, like other parts of Asia, the Green Revolution has helped the irrigated farmers in Pakistan to raise the productivity of their major crops, such as wheat, cotton, and rice. On the other hand, the rainfed I areas of Pakistan have drawn little benefit from the Green Revolution. The average yields achieved on the rainfed areas remain significantly lower than the yields derived by the traditional irrigated farmers. The rainfed farmers are also subject to subsistence farming conditions with per capita incomes well below the national average.2 Given the size of the area under rainfed conditions and the problems faced by the rainfed farmers, there have been attempts by the government, international donor agencies, and nongovernment organisations to come up with strategies to raise the productivity as well as income of the rainfed farmers. Such efforts, however, must take into account the production behaviour of the farm-households under rainfed conditions.